A study protocol to co-develop and evaluate interventions that strengthen healthcare resilience to extreme weather events in three African countries: the ASTRA study - Mabuto, Tonderai; Orievulu, Kingsley; Bond, Virginia; Simwinga, Musonda; Grapsa, Erofili; Khoza, Thandeka; Khan-Gillmore, Samantha; Nzimande, Londiwe; Craig, Marlies; Khagayi, Sammy; Chirwa, Taonga; Chiau, Rogerio; et al. (Frontiers in Climate, 2025)
Extreme weather events (EWEs) are becoming more frequent and intense due to climate change, disrupting healthcare systems and increasing risks for vulnerable populations. In low- and middle-income countries, these disruptions threaten progress in HIV and tuberculosis (TB) care by limiting access, straining services, and worsening health outcomes. Building health system resilience through environmentally sustainable infrastructure and processes, adequate and skilled workforce, and community engagement is essential to ensure continuity of care. In this four-year study (ASTRA), we aim to co-design, prioritise and evaluate interventions to strengthen community and health system resilience to EWEs for people living with HIV/TB. This multi-phase, mixed-methods study will be conducted in Mozambique, South Africa, and Zambia, countries which are highly vulnerable to EWEs such as storms, cyclones and flooding and bear a high burden of HIV and TB. Phase 1 will focus on understanding the context through stakeholder mapping, scoping interviews, a Delphi consensus process, and assessments of community and health facility vulnerability and adaptive capacity. We will carry out rapid ethnographic assessments [also known as Broad Brush Surveys (BBS)], spatial and statistical modelling, and a policy and programme analysis in this phase. Phase 2 will involve four sequential co-creation workshops in each country to produce prototype interventions that will be refined and prioritised for evaluation. In Phase 3, we will evaluate selected interventions using system dynamics modelling and economic analysis. Using systems dynamics modelling, we will model the final set of interventions, individually and in combination, to explore their potential effects on service delivery during EWEs. The economic evaluation will estimate the costs of inaction, assess the benefits of interventions through multi-criteria decision analysis, and determine their value for money to inform priority setting and policy action. Overall, the innovative use of participatory co-creation processes, system dynamics modelling, and economic evaluation, provides a model for designing and assessing adaptation interventions that are both evidence-based and locally relevant. ASTRA will inform national policy and planning and offer transferable knowledge for other climate-vulnerable settings facing similar challenges.